Exploratory analysis of metabolic changes using mass spectrometry data and graph embeddings - (:unkn) unknown (Nature Portfolio (Springer Nature), 2024)
Mass spectrometry (MS)-based metabolomics analysis is a powerful tool, but it comes with its own set of challenges. The MS workflow involves multiple steps before its interpretation in what is denominate data mining. Data mining consists of a two-step pr...
Keywords: Espectrometría de masas; Embeddings de grafos